ANALISIS TERHADAP INTEGRASI PENGETAHUAN DALAM SISTEM PENDIDIKAN DI SMP ISLAM TERPADU BUNAYYA - Dalimunthe, Irwan Saleh (Al-Hikmah: Jurnal Agama dan Ilmu Pengetahuan, 2021)
Knowledge integration is critical, for that it is necessary to build an integrated curriculum, namely a curriculum that has a link between revelation and science as well as an Islamic school environment arrangement. This is what SMP IT Bunayya does in educating its students. This study uses a qualitative approach with phenomenological methods. The research subjects were the principal and the school management, who handled the curriculum. Data was collected through interviews, document studies, and observation. Data processing is carried out by unit processing, categorization, and interpretation. The results showed that knowledge integration at SMP IT Bunayya was an integration model with two patterns: First, the model of integration into the curriculum package, namely the integration of aspects of cognitive, affective, psychomotor, etc., spirituality, and social values. Second, the model of integration into the lesson's themes, namely in the design of learning. Meanwhile, the coaching model to achieve the integrated curriculum is carried out with several activities: bina taqwa night, scouts, aqil baligh talk show, daily practice, and outing class.